Chronic genital ulcer disease with subsequent development of methicillin-resistant Staphylococcus aureus (MRSA) urethritis and bacteraemia in an HIV-seropositive person - a case observation - Christine Katusiime; Andrew Kambugu (AOSIS, 2012)
HIV-seropositive persons are at increased risk of methicillin-resistant Staphylococcus aureus (MRSA). Genital ulcerative disease and sexually transmitted infection with subsequent MRSA infection in HIV-seropositive persons have been documented only once. We report a case of a 44-year-old man who presented to the Infectious Diseases Institute, Kampala, Uganda, with chronic genital ulcer disease and who subsequently developed MRSA urethritis and bacteraemia. This case also demonstrates that persistent genital ulcer disease in HIV-seropositive persons may be as a result of concurrent MRSA infection.